Les gestionnaires et la négociation - Bourque, Reynald (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Les gestionnaires et la négociation," by David A. Lax and James K. Sebenius, édition française by Gilles Gauthier and Marie Thibault
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Negotiations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z